PENGARUH HARGA, PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. HONDA INDAKO BINJAI - Dachi, Rosa Ningsih; Saragih, Nawary; Simanhuruk, Peran (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study was to determine and explain the effect of price, promotion and brand image on purchasing decisions at PT. Honda Indako Binjai. Data collection was carried out by distributing questionnaires to 96 consumers who already owned a Honda Scoopy stylish sporty motorbike. Testing techniques used in research are validity testing, reliability testing, multiple linear regression analysis, hypothesis testing (F test and t test) and analysis of the coefficient of determination. Data analysis using SPSS version 22. From the results of the study showed multiple linear regression equations where: Y= 4.740+0.369X1+0.145X2+0.251X3+e. Simultaneously (F test) price, promotion, and brand image have a positive and significant effect on purchasing decisions (F-count of 50.344 > F-table 2.70). Partially (t test) the price has a positive and significant effect on purchasing decisions where t-count 5.545>t-table 1.66159 with a significant level of 0.000 t-table1,66159 with a significant level of 0.000 t-table 1.66159 with a significant level of 0.013